2020
DOI: 10.3390/catal10040442
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Designing Au Nanoparticles for Catalytic Epoxidation of Propylene with H2 and O2

Abstract: Au nanoparticles, which can be used in various industrial and environmental applications, have drawn substantial research interest. In this review, a comprehensive background and some insights are provided regarding recent studies concerning the use of Au nanoparticles for catalytic propylene epoxidation with H2 and O2. Over the last two decades, substantial progress has been made toward the efficient production of propylene oxide (PO); this includes the design of highly dispersed Au catalysts on Ti-modified m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Studies have shown that monomeric photocatalysts always lose their photocatalytic activity under the influence of inherent defects such as structural defects, photo corrosion, and rapid recombination of charge carriers produced by light. There are some ways to improve the photocatalytic activity of monomers that can be useful for the industrialization of photocatalysts [117]. For this purpose, conventional methods such as heterogeneous fabrication with other metals, combination with semiconductors, molecular and elemental doping and preparation of nanocomposite have been used so far [118].…”
Section: Co2 Reductionmentioning
confidence: 99%
“…Studies have shown that monomeric photocatalysts always lose their photocatalytic activity under the influence of inherent defects such as structural defects, photo corrosion, and rapid recombination of charge carriers produced by light. There are some ways to improve the photocatalytic activity of monomers that can be useful for the industrialization of photocatalysts [117]. For this purpose, conventional methods such as heterogeneous fabrication with other metals, combination with semiconductors, molecular and elemental doping and preparation of nanocomposite have been used so far [118].…”
Section: Co2 Reductionmentioning
confidence: 99%
“…[12][13][14][15] More generally, the design and engineering of catalysts that selectively activate carbon-hydrogen bonds to produce desired products are still not in the reach of green chemistry. [26][27][28] Only recently, few selective solvent-free processes for conversion of toluene to benzoic acid using Ca 2 Sb 2 O 7 , Co-MOF-74@NDHPI, and Co@N/Co-CNT catalysts have been reported. [16][17][18] Moreover, the graphene oxides (GO) with different metal-based architectural designs have been applied for different oxidation reactions such as CO and alcohol oxidation and water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] However, developing catalysts that selectively activate carbon-hydrogen bonds and modify reaction pathways to produce desired products is still challenging in green chemistry. [26][27][28] The entropy stabilization concept has triggered an extensive research interest in exploring the vast compositional space provided by multicomponent materials containing four or more elements. Such multicomponent materials usually crystallize into a single-phase solid solution and exhibit a superior combination of properties compared to conventional solid solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct gas‐phase epoxidation of propylene with H 2 and O 2 over Au‐Ti catalysts has attracted considerable interests for clean and economical production of propylene oxide (PO) compared to the traditionally industrial processes 1–4 . Among the tested catalysts, the Au nanoparticles immobilized on uncalcined TS‐1 have exhibited state‐of‐the‐art PO formation rate and stability by avoiding the deactivation caused by micropore blocking 5–7 .…”
Section: Introductionmentioning
confidence: 99%